Design and biomechanical performance analysis of a user-friendly orthotic device - Rakib, Muhammad Iftekharul; Choudhury, Imtiaz Ahmed; Hussain, Sajjad; Abu Osman, Noor Azuan (Elsevier, 2015)
Material selection and proper design are essential for developing a new product, especially biomedical devices. Stance-control-orthosis (SCO) are walking assistive device for the patients with weak quadriceps. This manuscript presents the development of a prefabricated SCO with suitable material and design. It is 45 lighter than commercially available prefabricated device. It contains some adjustable features to make it competent for wide range of patients in terms of height (153-183 cm) and weight. Finite element analysis (FEA) was used for selecting the best material and optimizing weight of different components of this device. Basic structures the device were made of aluminum alloy 7075-T6. Carbon-fiber epoxy composite material was used for fabricating the support braces of the device and a polypropylene made foot part was included. Components were fabricated according to FEA results and had been evaluated by mechanical tests. Almost similar results of FEA were found during mechanical tests. The device gait performance was assessed and compared with commercially available prefabricated SCO. The results revealed a better gait. Proper material selection and design made this orthotic device light, structurally stable, functionally suitable and cosmetically acceptable to users. (C) 2014 Elsevier Ltd. All rights reserved.